COMPARAÇÃO DAS PROPRIEDADES ELETRÔNICAS DO TRIADIMEFON E DE SEU METABÓLITO TRIADIMENOL (CIPEEX, 2026)
Pesticides are widely used in agriculture but present risks associated with their toxicity. Among them, triazole fungicides stand out for their efficacy and broad spectrum of action, acting to inhibit ergosterol biosynthesis in fungi. In this study, the physicochemical and electronic properties of triadimefon (TDF) and its metabolite, triadimenol (TDN), were investigated using Density Functional Theory (DFT) calculations. The molecular structures were optimized using the M06-2X functional and the 6-311++G(d,p) basis set, followed by frequency analysis and determination of reactivity descriptors. The results showed that TDN exhibits greater electronic stability due to its increased HOMO-LUMO gap, while TDF is characterized by greater reactivity and electronic adaptability, favoring its interaction with enzymatic targets. Both compounds were classified as strong electrophiles, suggesting potential for selective interactions with nucleophilic biomolecules. These findings contribute to a better understanding of the structural and reactivity differences between TDF and TDN, providing insights for the safer and more effective use of these fungicides in agriculture.
Keywords: Fungicides; Triadimefon; Triadimenol; Density Functional Theory.